Under the Hill, and Other Essays in Prose and Verse - Beardsley, Aubrey, 1872-1898 (Salt Lake City, UT : Project Gutenberg, 2015)
"Under the Hill, and Other Essays in Prose and Verse" by Aubrey Beardsley is a collection of whimsical literary pieces along with illustrations created during the late 19th century. This unique work blends elements of prose and verse, showcasing Beardsley's characteristic wit and artistry rooted in the Decadent movement. The collection is likely to resonate with readers interested in exploring themes of romanticism, decadence, and the complex interplay between art and literature. The book's centerpiece, "Under the Hill," follows the journey of the Abbé Fanfreluche as he navigates a magical and sensory landscape filled with enchanting characters, such as Helen and her lavishly adorned entourage. Fanfreluche's interactions manifest the interplay of beauty, artifice, and desire, illustrated with Beardsley's distinctive style, blending elegance and grotesque elements. The anthology further includes poems, translations, and memorable letters that elucidate Beardsley's thoughts on art and literature, offering a glimpse into his brilliant yet tragic mind as a significant figure in late Victorian literature and art. (This is an automatically generated summary.)
Under the hill -- The three musicians -- The ballad of a barber -- Translation of Catullus: Carmen CI -- Table talk of Aubrey Beardsley -- Two letters of Aubrey Beardsley.
Release date is 2015-09-26
Produced by Marc D'Hooghe (Images generously made available at the Internet Archive.
Keywords: English literature -- 19th century; Beardsley, Aubrey, 1872-1898